Degradação do herbicida diuron por bactérias isoladas de solos de cultura de cana-de-açúcar e avaliação da toxidade dos metabolitos gerados sobre peixes - Silva, Pedro Lucas Bueno da [UNESP] (2015)
The intensification of agriculture has led an increase in the use of pesticides, which may carry these compounds and their derivatives from soil to aquatic environments. To minimize the presence of xenobiotics in the environment, it has been suggestes bioremediation techniques that use the activity of microorganisms to eliminate or reduce these pollutants. The attack of aromatic and chlorinated compounds by microorganisms or their enzymes free in the medium can lead to desirable biodegradation process, yielding chemically simpler and less toxic derivatives until the total mineralization of the compound. The aim of this work was to study the degradation of diurom by bacterial strains previously isolated from cane sugar cultivation of soils with application history of this herbicide in submerged fermentation and in microcosms and evaluate the toxicity of diuron derived from compounds generated by metabolism microbial. All bacteria tested were able to grow in the presence of diuron, but not all were able to degrade it when cultured in liquid medium. When used in a soil cultivation systems plus diuron (microcosms) afforded 50% compound. In the tests of toxicity of the metabolites of diuron was used fish the enzymatic activity of 7-O-etoxiresorufina deetilase (EROD) and comet assay as a reference. Was observed inhibition of EROD activity, possibly related to...